Land Use - Principe, Jeark A. (UPCOE NEC Technical Bulletin)
This paper presents the results of using a series of moderate resolution (30m) Landsat images to derive a general land use/land cover (LULC) map of the islands of Panay, Guimaras and portions of Negros. The said images were pre-processed for atmospheric correction, cloud and cloud shadow filling and removal of noisy pixels. The six optical bands of Landsat ETM+ and an additional built-up index band were used as inputs to image classification, in per scene basis, via the Maximum Likehood classifier. The said index band was derived from the three original Landsat bands and was used to aid in differentiating built-up and bare soil pixels. The classified image has a mean overall accuracy of 85.41% and kappa coefficient of 0.819 while derived LULC map from this classification showed a class distribution of bare soil, paddy fields, forest, built-up, grass and water areas covering 33.4%, 11.3%, 13.3%, 2.2%, 30.5% and 9.3% of the total area of the three Philippine islands. The study demonstrated the use of freely-available moderate resolution Landsat images to derive LULC maps, a very important spatial data that is often used in many research studies dealing with environmental planning and protection.